PENERAPAN METODE SIMULASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PKN SISWA DI SD NEGERI 187/IV KOTA JAMBI - Siregar, Juniar (Jurnal Dinamika Pendidikan, 2016)
This study presents a research report on using simulation method to improve the activity and the studentsâ learning result improving studentsâ Learning results on PKn. The objective was to find out whether the activity and the studentsâ learning result improved when they are taught by using Video. It was conducted using classroom action research method. The subject of the study was the Grade IV students of SDN 187/IV Kota Jambi which is located on Jln. Adi Sucipto RT 05 Kecamatan Jambi Selatan, and the number of the students were 9 persons. The instruments used were test as quantitative data and observation, interview, and questionnaire were used as qualitative data. In analyzing the data, the mean of the studentsâ score for the on first cycle was 74.11 and the mean on cycle two was 78.00 and the mean of the third cycle was 84.7. Then it can be concluded that the use of simulation as a learning method can improve the studentsâ activity and studentsâ learning result. It is suggested that teachers should apply simulation method as a learning method to improve studentsâ activity and studentsâ learningresult on PKn.Keywords : PKn, studentsâ activity, studentsâ learning results, simulation method